Comparison between mood states, stress and recovery in CrossFit® competitors and non-competitors - D’alpino, Isabela Ambrósio; Moterosso, João Paulo Campanhã; Botaro, Weligton Rodrigo; DA SILVA, Alini Oliveira Cassiano; Sant’anna, Paula Grippa; Testa Junior, Ademir; Verardi, Carlos Eduardo Lopes [UNESP]; Zanini, GABRIEL DE SOUZA [UNESP] (My University, 2022)
Currently, there is an increase in the demand for sports and physical exercises, which are the most effective way to promote health, self-esteem and prevent bad habits. In this context, the practice of CrossFit® attracts new practitioners every day, given the expectation of the challenge linked to the practice due to high intensity training, in this sense still, many feel attracted to competitions in the modality. However, high training loads associated with demands can bring changes in the level of stress associated with abrupt changes in mood. Thus, the present study aims to identify and analyze levels of stress and recovery, and the mood of CrossFit® competitors and non-competitors. The BRUMS instrument was used to measure the mood level and the RESTQ 76 to determine the levels of stress and recovery. The results demonstrate that there was a difference between the pre-competitive and competitive periods for the group of competitors for the variables tension (48.27 ± 36.36%, p = 0.05) and post-competition (79.31 ± 20.45%, p = 0.002), intergroup difference during the competitive period for depression [1380 ± 180.64%, X²(2) = 3.961, p = 0.05]; changes in anger were observed during pre-competitive and competitive periods (247.93 ± 33.14%, p = 0.041) for the competitive group, and during the recovery period (43.38 ± 27.64%, p = 0.048), in addition, difference between the analysis groups [109.45 ± 34.83%, X² (2) = 3.116, p = 0.043], vigor showed a significant reduction for the competitor group, and, intergroup difference during the study [X² (2) = 4,685; p = 0.03], in addition, there was a difference between groups for confusion (406.97 ± 25.98%, f = 4.707, p= 0.041); in the stress analysis, the specific stress showed a difference for the competitor group (31.15 ± 15.78%, p = 0.021), in addition to demonstrating a difference in the analysis between groups (39.94 ± 25.54%, f = 7.321, p = 0.019), the global stress in turn, it showed a difference between the groups (43.77 ± 36%, f = 5.068, p = 0.44). The data therefore demonstrate that CrossFit practitioners submitted to periods of competition have changes in their mood profile and stress levels when compared to non-competitive individuals submitted to the same training routines.
Keywords: Competitor; CrossFit; Mood States; Recovery; Stress